Ancient Maya commoners - Lohse, Jon C., 1968-; Valdez, Fred, Jr., 1953- (University of Texas Press, 2004)
"This book marshals a wide array of archaeological, ethnohistorical, and ethnographic evidence to offer the fullest understanding to date of the lifeways of ancient Maya commoners. Thirteen senior and emerging scholars contribute case studies that examine such aspects of commoner life as settlement patterns, household organization, and subsistence practices. Their reports cover most of the Maya area and the entire time span from Preclassic to Postclassic. This broad range of data helps resolve Maya commoners from a faceless mass into individual actors who successfully adapted to their social environment, responding to the economic, political, and ideological pressures exerted on them by the elites, and who also held primary responsibility for producing the food and many other goods on which the whole Maya society depended."--Provided by publisher